Opposite roles of myocardin and atrogin‐1 in L6 myoblast differentiation1. Issue 10 (20th June 2013) - Jiang, Yulan; Singh, Pavneet; Yin, Hao; Zhou, Yi‐Xia; Gui, Yu; Wang, Da‐Zhi; Zheng, Xi‐Long; ,; ,
Abstract L6 rat myoblasts undergo differentiation and myotube formation when cultured in medium containing a low‐concentration of serum, but the underlying mechanism is not well understood. The role of atrogin‐1, an E3 ligase with well‐characterized roles in muscle atrophy, has not been defined in muscle differentiation. Myocardin is a coactivator of serum response factor (SRF), which together promotes smooth muscle differentiation. Myocardin is transiently expressed in skeletal muscle progenitor cells with inhibitory effects on the expression of myogenin and muscle differentiation. It remains unknown whether myocardin, which undergoes ubiquitination degradation, plays a role in L6 cell differentiation. The current study aimed to investigate the potential roles of myocardin and atrogin‐1 in differentiation of L6 cells. As reported by many others, shifting to medium containing 2% serum induced myotube formation of L6 cells. Differentiation was accompanied by up‐regulation of atrogin‐1 and down‐regulation of myocardin, suggesting that both may be involved in muscle differentiation. As expected, over‐expression of atrogin‐1 stimulated the expression of troponin T and myogenin and differentiation of the L6 myoblasts. Co‐expression of myocardin with atrogin‐1 inhibited atrogin‐1‐induced myogenin expression. Over‐expression of atrogin‐1 decreased myocardin protein level, albeit without affecting its mRNA level. Small‐interfering RNA‐mediated knockdown of atrogin‐1 increased myocardin protein. Consistently, ectopic expression of myocardin inhibited myogenic differentiation. Unexpectedly, myocardin decreased the expression of atrogin‐1 without involving Foxo1. Taken together, our results have demonstrated that atrogin‐1 plays a positive role in skeletal muscle differentiation through down‐regulation of myocardin. J. Cell. Physiol. 228: 1989–1995, 2013. © 2013 Wiley Periodicals, Inc.